A driver assistant system for improvement of passenger ride comfort through modification of driving behaviour - Wang, F; Ma, N; Inooka, H (IEE conference publication, 2001)
In recent years, using automobiles for transportation becomes an unavoidable part of one's daily life. For example, Japanese governmental statistics shows that Japanese people traveled on average about 7500 kilometers in the fiscal year of 1999 as drivers or passengers of automobiles. Hence, improving the ride comfort of automobiles becomes a subject of increasing importance. The ride discomfort caused by velocity fluctuation is studied. A ride discomfort index (RDI) and a model that estimates the RDI are proposed. Furthermore, based on the assumption that by improving his/her driving skills and modifying his/her driving behaviour, a driver can control the velocity fluctuation of an automobile to reduce the RDI and thus can improve the passenger ride comfort. A driver assistant system that estimates the RDI and feeds it back in real time to the driver is developed. Its function in reducing the RDI is tested through experiments. The aim of the study is to assist the driver in modifying his/her driving skills and driving behaviour to reduce passenger ride discomfort and thus provide passenger-friendly maneuvers.